Importance Of Coherence and Cohesion in Writing - Barakatova Dilorom Aminovna (Genius Journals, 2022)
This article defines the most effective and useful ways of teaching academic writing and to identify the significance of cohesion and coherence in academic writing .
Keywords: Cohesion; Unlinked; Coherence; Writing Quality